The influence factors of e-logistics implementation in China: The conceptual framework - Lisha, Guo; A Jalil, Emy Ezura; Zainuddin, Nizamuddin (2018)
Since from last decade, the e-logistic industry of China facing different issues due to high volume worldwide.To address this issue, this study introducing a framework to mitigate various issues of e-logistic in China. Therefore, the prime objective of the current study is to examine the factors influencing e-logistics in China.To achieve this objective, the current study examines the effect of distribution rate, transit time, payment and information and communication technology (ICT) on e-logistic.It is found that distribution rate and transit time has a significant positive relationship with e-logistic. Moreover, it is found that ICT playing a mediating role between payment and e-logistic. Hence, this study contributes to the body of knowledge by introducing a research framework to enhance the performance of e-logistic, particularly in China. Furthermore, this research study introduced information and communication technology (ICT) by updating the concept of IT (information technology).Thus, the current study is beneficial for the e-logistic industry to enhance the performance by employing the current model.